First-Hand Accounts of Suicidal Mental Imagery: A Taxonomy of Imagery Types - Keogh, Brian; Doyle, Louise (My University, 2026)
Suicidal mental imagery are self-generated images of injury and death experienced across a range of mental health conditions, but also experienced in people who have no diagnosable mental health condition. For some, these images can be quite distressing and unwanted, but for others, these mental pictures serve to bring comfort and problem-solving capabilities. From a clinical and research perspective, they are not fully understood and are underexplored. Suicidal mental imagery is a known risk factor for attempted suicide due to imagery’s amplification and habituation effects, potentially moving a person from imagining suicide to acting on it. This paper presents a taxonomy of the different types of suicidal mental imagery from first-hand accounts extracted from phase one of a two-phase qualitative study called the suicidal mental imagery (SUMI) study. This taxonomy of imagery types is drawn from fifteen semi-structured interviews exploring imagery experiences in adults from Ireland. The characteristics of these images were analysed qualitatively using an Interpretive Description approach, with the resulting taxonomy developed through additional analytic processes informed by cognitive behavioural therapy (CBT) principles and a priori coding. The taxonomy, therefore, illustrates experiences from a rich dataset under distinct categories to improve our understanding of the key mechanisms underpinning suicidal mental imagery for practice, helping to assist open dialogue in imagery assessment to better inform suicide prevention interventions.
PUBLISHED
Keywords: assessment and treatment; CBT suicide prevention (CBT-SP); cognitive behavioural therapy (CBT); comfort; distress; suicidal mental imagery (SUMI); suicide prevention; taxonomy